The effect of self-management empowerment model on the sense of coherence among elderly patients with cardiovascular disease. Issue 2 (1st February 2016) - Musavinasab, Maryam; Ravanipour, Maryam; Pouladi, Shahnaz; Motamed, Niloofar; Barekat, Maryam
Abstract: To correct poor quality of life due to the elderly's limitations and cardiovascular disorders requires the identification of supporting resources, adaptation, and enhancement of the sense of coherence. While having the little evidence available, this clinical trial was performed on 96 elderly people with cardiovascular disease. The goal was to determine the effect of education based on a self-management empowerment model on the sense of coherence. The results indicate the effect of a five-step educational intervention on a total sense of coherence score in the experimental group and on its dimensions. The results can provide a framework to design nursing education for the empowerment of the elderly.